Evidence for the Postconquest Demographic Collapse of the Americas in Historical CO 2 Levels - Faust, Franz Xaver; Gnecco, Cristóbal; Mannstein, Hermann; Stamm, Jörg (American Meteorological Society, 2006)
This article promotes the hypothesis that the massive demographic collapse of the native populations of the Americas triggered by the European colonization brought about the abandonment of large expanses of agricultural fields soon recovered by forests, which in due turn fixed atmospheric CO 2 in significant quantities. This hypothesis is supported by measurements of atmospheric CO 2 levels in ice cores from Law Dome, Antarctica. Changing the focus from paleoclimate to global population dynamics and using the same causal chain, the measured drop in historic atmospheric CO 2 levels can also be looked upon as further, strong evidence for the postconquest demographic collapse of the Americas.